BIMBINGAN TEKNIS TEKNOLOGI MORTAR DENGAN CAMPURAN FLY ASH UNTUK INDUSTRI PAVING BLOCK DI KELURAHAN KESSILAMPE KOTA KENDARI - Romy Suryaningrat Edwin; Minson Simatupang; Fitriah Masud; Masykur Kimsan; Asminar Azis Nugraha; Nasrul Nasrul; Irmawatty Paula Tamburaka (LP2M Universitas Hasanuddin, 2021)
Abstract. This community service aimed to guide industrial partners in producing building materials i.e. paving blocks, containing fly ash as cement replacement. This activity was performed in several stages, (1) conducting a partner’s site visit to discern the production process in association with the types of equipment and the type of utilized materials. (2) Making provision for service activities through team briefing and preparation; (3) Producing a K200 paving block mixture design to which the service team would advocate industry partners; (4) Elucidating the benefits of fly ash instead of cement and purveying technical guidance for the manufacture of paving blocks with a mixture of fly ash. The results evinced a partner’s understanding of the performance of fly ash as a cement substitution material that can increase the strength of the paving block rather than using the entire cement. The mix design composition, recommended by the allegiance team, was used as a reference by Mitra Industri in manufacturing K200 paving blocks. Partners have also been able to demonstrate the method of mixing materials to make paving blocks faster than their conventional method, hence the production of paving blocks increases. Abstrak. Pengabdian masyarakat ini bertujuan untuk membimbing mitra industri yang memproduksi bahan bangunan dalam membuat paving block dengan campuran fly ash sebagai pengganti semen. Pengabdian ini dilakukan dalam beberapa tahapan, (1) melakukan survey lokasi untuk melihat proses produksi terkait peralatan dan material yang digunakan; (2) persiapan tim melakukan kegiatan pengabdian; (3) tim membuat rancangan campuran paving block K200 yang akan direkomendasikan ke mitra industri; (4) tim pengabdian menjelaskan keuntungan dari fly ash sebagai pengganti semen dan melakukan bimbingan teknis untuk pembuatan paving block dengan campuran fly ash. Hasil yang peroleh adalah mitra memahami kinerja fly ash sebagai bahan substitusi semen yang dapat meningkatkan kekuatan paving block melebihi dibandingkan menggunakan semen keseluruhan. Komposisi mix design yang direkomendasikan tim pengabdian dijadikan rujukan oleh mitra industri untuk pembuatan paving block mutu K200. Mitra juga sudah dapat mendemonstrasikan metode pencampuran material untuk membuat paving block yang memiliki durasi waktu lebih cepat sehingga produksi paving block meningkat.